Assembly of vesicular stomatitis virus: distribution of the glycoprotein on the surface of infected cells. - Jacobs, B L (1982)
This study demonstrates that the glycoprotein of vesicular stomatitis virus clusters in the plasma membrane of infected Chinese hamster lung cells during morphogenesis and suggests that viral nucleocapsids are required for this clustering. A mutant virus (ts E-1) which is temperature sensitive for the synthesis of viral nucleocapsids but not viral membrane proteins was used. The surface distribution of the viral glycoprotein in cells infected by this virus was determined by a specific indirect immunoferritin stain. Early in infection at permissive temperatures, the glycoprotein was randomly distributed on membrane ghosts. Later, clusters of ferritin the size and shape of virus particles were seen. In contrast, ghosts prepared from virus-infected cells maintained at a restrictive temperature always had a random distribution of viral glycoprotein.